Efecto de Benlatey Cupravit sobre el Combate de la Moniliasis y Mancha de Agua del Cacao - Meza Sanoja, Carlos (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2014)
The fungicides Benlate at the rates of 250, 500 and 750 grams per hectare and Cupravit at the rate of 2.500 grams per hectare were compared under field conditions for the control of “moniliasis” and water spot in cacao. There was a significant difference between the rates and intervals of application of Benlate. This could be due to the high incidence of Mecistorrhinus tripterus F. There were significant differences in the control of water spot with the fungicide Cupravit and the intermediate rate of Benlate. In accordance with the results of this study, it can be assumed that the fungicide Benlate díd not have systemic properties. The total production of fruit was greater with the fungicide Benlate and it had a tendency to increase when greater concentrations of the fungicide were used. In the plants treated with Cupravit therewas was a notable reduction in the number of fruits formed in comparison with the plants treated with Benlate. The number of fruits formed was greater at three weeks than at two weeks. Based on field observations, there is a higher incidence of moniliasis in plants that receive more light.